Pengaruh Profitabilitas, Leverage, Likuiditas, dan Ukuran Perusahaan Terhadap Ketepatan Waktu Pelaporan Keuangan - Putri, Tiara Herawati; Nugroho, Lucky (ARBITRASE: Journal of Economics and Accounting, 2023)
This study examines the factors that potentially affect the timeliness of financial reporting. These factors include profitability, leverage, liquidity, and company size. The population in this study are cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. Quantitative research is used as a research design, and purposive sampling is used as a sampling method in this study. The total sample in this study was 60 companies from 122 companies that met the criteria, so 300 observation data were obtained. The data used is secondary data, and the data analysis technique to test the hypothesis in this study is the logistic regression analysis method. Based on the results of the study shows that simultaneously, profitability, leverage, liquidity, and company size affect the timeliness of financial reporting. Partially, profitability and leverage positively and significantly affect the timeliness of financial reporting. While liquidity and company size partially have an insignificant effect on the timeliness of financial reporting. The implication of this research is to provide information and add to the scientific repertoire for practitioners and academics related to the timeliness of financial reporting. The novelty of this research is related to the potential factors on the timeliness of financial reporting from cyclical consumer companies listed on the IDX in the 2017-2021 period